Glycerol: An Optimal Hydrogen Source for Microwave-Promoted Cu-Catalyzed Transfer Hydrogenation of Nitrobenzene to Aniline - Moran, Maria Jesus; Martina, Katia; Stefanidis, Georgios D.; Jordens, Jeroen; Gerven, Tom Van; Goovaerts, Vincent; Manzoli, Maela; Groffils, Carlo; Cravotto, Giancarlo (Frontiers in Chemistry, 2020)
The search for sustainable alternatives for use in chemical synthesis and catalysis has found an ally in non-conventional energy sources and widely available green solvents. The use of glycerol, an abundant natural solvent, as an excellent “sacrificial” hydrogen source for the copper-catalysed microwave (MW)-promoted transfer hydrogenation of nitrobenzene to aniline has been investigated in this work. Copper nanoparticles (CuNPs) were prepared in glycerol and the efficacy of the glycerol layer in mediating the interaction between the metal active sites has been examined using HRTEM analyses. Its high polarity, low vapour pressure, long relaxation time and high acoustic impedance mean that excellent results were also obtained when the reaction media was subjected to ultrasound (US) and MW irradiation. US has been shown to play an important role in the process via its ability to enhance CuNPs dispersion, favour mechanical depassivation and increase catalytic active surface area, while MW irradiation shortened the reaction time from some hours to a few minutes. These synergistic combinations promoted the exhaustive reduction of nitrobenzene to aniline and facilitated the scale-up of the protocol for its optimised use in industrial MW reactors.